1989
DOI: 10.1128/jvi.63.10.4129-4135.1989
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Marek's disease virus tumorigenicity is associated with truncation of RNAs transcribed within BamHI-H

Abstract: The attenuation of Marek's disease virus (MDV) is associated with loss of pathogenicity and tumorigenicity. Previous studies have demonstrated a strong correlation between attenuation and amplification of a specific sequence located within the MDV terminal and internal repeats. We recently reported that the regions containing the amplified sequences, the BamHI D and H fragments, were transcriptionally active. However, differential transcription activity was observed to exist between attenuated and pathogenic M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Oncogenic MDV strains do not replicate well in cell culture and become attenuated rapidly during serial passage (10). Attenuation is accompanied by alterations in the sequence and expression of the MDV genome (3,4,13,21,41,44), loss of horizontal transmission (10), and a decreased ability to infect lymphocytes in vivo and in vitro (39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oncogenic MDV strains do not replicate well in cell culture and become attenuated rapidly during serial passage (10). Attenuation is accompanied by alterations in the sequence and expression of the MDV genome (3,4,13,21,41,44), loss of horizontal transmission (10), and a decreased ability to infect lymphocytes in vivo and in vitro (39).…”
mentioning
confidence: 99%
“…These approaches have led to the identification of a number of MDV genes and regions having possible significance for transformation. The repeats (terminal and inverted, respectively) flanking the unique long (UL) region of the MDV genome (TR L and IR L ) encode a family of RNAs that become disrupted during attenuation (3,4). This region also contains the meq gene, which encodes a leucine-zipper-containing protein expressed in LBCLs (18).…”
mentioning
confidence: 99%
“…Several laboratories demonstrated that the amplification of a 132-bp repeat in this region during prolonged passages of MDV correlates with the attenuation of viral oncogenicity (15,25,37). Bradley et al (3,4) further showed that expansion of this region results in the disruption of a 1.8-kb transcript(s) and suggested that this transcript is involved in MDV-induced transformation. Other transcripts that are initiated or terminated near the 132-bp repeat region have also been described (6).…”
mentioning
confidence: 99%
“…To further characterize this antigen, we proceeded to identify two Xgtll (gtll) clones (GA8 and RA2), derived from the MDV genome, that react with this monoclonal antibody (9). These two clones map within the BamHI H fragment at a region close to the 1.8-kb transcription unit (3,4,20). We also raised antisera against the recombinant B-galactosidase-MDV fusion proteins of these two clones.…”
mentioning
confidence: 99%
See 1 more Smart Citation